Spinal Neurocytoma: A Case Report and Review of Literature - Guedira, Khalil; Matar, Nidhal; Salem, Maher Ben; Chelly, Ines; Zemmel, Ihsen (Indian Journal of Neurosurgery, 2017)
Extraventricular locations of neurocytoma are extremely rare, especially in the spinal cord, which has been reported in only sporadic cases. In this article, we report a new pediatric case of a spinal neurocytoma in a 12-year-old girl and briefly review the relevant literature.
Keywords: neurocytoma; extraventricular; spine